A Qualitative Exploration of Intentional Indirect Self-Harm on Adolescents - Niazi, Rehana Batool; Rohail, Iffat (Annals of Human and Social Sciences, 2024)
The purpose of this study is to investigate the causes and manifestations of intentional indirect self-harm among adolescents in Islamabad and Rawalpindi, Pakistan. By diving into adolescents’ personal experiences and perceptions, A qualitative method was used to acquire a thorough knowledge of adolescents’ experiences and attitudes on indirect self-harm. Semi-structured interviews were performed with a purposively selected sample of adolescents aged 13 to 19 from various schools and localities in Islamabad and Rawalpindi. Thematic analysis was used to discover reoccurring themes and patterns about the motivations, circumstances, and consequences of indirect self-harm. The study identified numerous major themes Innetional indirect self-harm , including the secondary themes include various intentional indirect self-harm behaviors such as injuries, hitting, cuts, overeating, snatching, drug usage, fast driving, punching, vomiting, motorbike driving, frustration, emotional distress, and smoking.The Adolescents reported engaging in these activities as coping methods in response to mental discomfort, a lack of parental support, and feelings of inadequacy. The study also found that cultural stigmas around mental health and a lack of supportive services are significant obstacles to obtaining treatment. The government and mental health professionals should work together to establish a supportive atmosphere that promotes open discussions about mental health and equips teenagers with the tools and resources they need to deal with stress and emotional issues in a healthy and productive manner.